Study of the Elastic Scattering in the d + 11B system for EBS purposes - Tsakiris, Theofanis; Kokkoris, Michael; Maragkos, Fotis; Ziagkova, Anastasia; Dimitrakopoulos, Nikolaos; Krmpotić, Matea; Cosic, Donny; Provatas, Georgios; Lagoyannis, Anastasios (HNPS Advances in Nuclear Physics, 2022)
The implementation of boron in several fields, such as in the creation of p-type semiconductors in electronics, has created the need for the accurate quantitative determination of its depth profile concentrations in near surface layers of various matrices. In the framework of IBA techniques a combination of Elastic Backscattering Spectroscopy, along with Nuclear Reaction Analysis, has been proposed in order to address the current needs for boron depth profiling, focusing on the use of proton beams. Deuteron beams however offer superior mass resolution with similar stopping power values and simultaneous excitation of most light elements. Unfortunately, the lack of experimental datasets concerning the deuteron elastic scattering on boron impedes their use. Thus, in the present work, the first set of measurements for the 11B(d,d0) differential cross section covering the Ed,lab=1300-1860 keV energy range for the backscattering angles of 150ο, 160ο and 170ο were carried out. The study was conducted at the 5.5 MV Tandem Accelerator of the Institute of Nuclear and Particle Physics, in the National Center of Scientific Research “Demokritos”, Athens, Greece. The target was a thin, self-supporting aluminum foil, upon which a thin natB (isotopic ratio: 11B 80.1%, 10B 19.9%) layer was deposited using the sputtering technique at RBI, Zagreb, Croatia, followed by the evaporation of an ultra-thin layer of 197Au on top for normalization and wear protection purposes. The outgoing particles were detected using silicon surface barrier (S.S.B.) detectors and the differential cross sections for elastic scattering were determined from the resulting spectra via the relative technique